Differences of DNA methylation patterns in the placenta of large for gestational age infant. Issue 39 (25th September 2020) - Shen, Zheng; Tang, Yanfei; Song, Yemei; Shen, Wenxia; Zou, Chaochun
Abstract : Abstract: To investigate the molecular mechanisms of later metabolic health changes in large for gestational age (LGA) newborns by analyzing deoxyribonucleic acid (DNA) methylation patterns in the placenta of LGA and appropriate for gestational age (AGA) newborns. A total of 6 placentas of LGA and 6 placentas of AGA newborns were enrolled as LGA group and AGA group. DNA methylation was analyzed using the Illumina Infinium Human MethylationEPIC BeadChip microarrays and verified via pyrosequencing and reverse transcription-quantitative real-time polymerase chain reaction. Functional enrichment analysis were constructed by gene ontology and Kyoto Encyclopedia of Genes and Genomes pathway analysis based on the differentially methylated regions between LGA and AGA groups. Clinical investigation showed that LGA newborns had significantly lower hemoglobin and blood glucose compared to AGA newborns. Birth weight was negatively correlated to hemoglobin and blood glucose. Genome-wide DNA methylation analysis identified 17 244 methylation variable positions achieving genome-wide significance (adjusted P < .05). 34% methylation variable positions were located in the gene promoter region. A total of 117 differentially methylated regions were revealed by bump hunting analysis, which mapped to 107 genes. Function analysis showed 13 genes enriched in "adhesion and infection process, endocrine and other factor-regulated calcium reabsorption, calcium signaling pathway and transmembrane transport". Four genes linked to type II diabetes mellitus. Among the 13 genes, we selected GNAS and calcium voltage-gated channel subunit alpha1 G for independent verification of pyrosequencing, and the messenger ribonucleic acid levels of guanine nucleotide binding protein, calcium voltage-gated channel subunit alpha1 G, DECR1, and FK506 binding protein 11 were verified by reverse transcription-quantitative real-time polymerase chain reaction. DNA methylation variation and gene expression differences in placental samples were associated with LGA newborns, which linking the effect of intrauterine environment to regulation of the offspring's gene expression. Furthermore, pathway analysis suggested that intrauterine environment affecting fetal growth might had a functional impact on multiple signaling pathways involved in fetal growth, metabolism, and inflammation. Further studies were required to understand the differences of methylation patterns. Abstract : Supplemental Digital Content is available in the text